Fast-wave analysis of an inhomogeneously-loaded helix enclosed in a cylindrical waveguide - summary - Ghosh S.; Jain P.K.; Basu B.N. (My University, 2025)
The inhomogeneously-loaded helix enclosed in a metal cylindri- cal waveguide operated in the fast-wave regime is field-analyzed using the tape-helix model. The inhomogeneous discrete dielectric supports have been modeled by azimuthally smoothing them out into a number of continuous, homogeneous dielectric tube regions of appropriate effective relative permit- tivity values determined by the relative volumes occupied by the supports in these regions. While accounting for the radial inhomogeneity, the non- uniformity of the radial propagation constant over the structure cross section is also taken into consideration. Further, structured expressions amenable to easy computation are presented with the help of the relevant recurrence relations, and a method is suggested to use them in an iterative cycle for the desired convergence accuracy. The dispersion relation developed, as a special case, passes on to that obtained elsewhere for a simpler structure in which the dielectric supports for the helix was not considered. It is observed that the dielectric-support parameters become more effective in controlling the dispersion curve than the bare helix parameters. It is also found that the effect of the controlling parameters such as the helix pitch angle on the phase velocity and interaction impedance of the structure becomes less pronounced as the helix is brought closer to the waveguide wall. The pres- ence of the dielectric in the structure increases the value of the interaction impedance to a reasonable value over the entire operating frequency band. The results in terms of the structure parameters, namely, helix pitch angle, helix-support permittivity, helix-to-waveguide wall separation and structure inhomogeneity presented here are rather general, and can be used for the structure design and performance evaluation as well as for the control of any space harmonic of interest in a fast-wave device such as the gyro-traveling- wave amplifier. © Journal of electromagnetic waves and applications. All Rights reserved.